2010
DOI: 10.2353/ajpath.2010.090430
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Hyperplasia Associated with Discordant Xenogeneic Parenchymal-Nonparenchymal Interactions in Human Hepatocyte-Repopulated Mice

Abstract: Liver mass is optimized in relation to body mass. Rat (r) and human (h) hepatocytes were transplanted into liver-injured immunodeficient mice and allowed to proliferate for 3 or 11 weeks, respectively, when the transplants stopped proliferating. Liver/body weight ratio was normal throughout in r-hepatocytebearing mice (r-hep-mice), but increased continuously in h-hepatocyte-bearing mice (h-hep-mice), until reaching approximately three times the normal m-liver size, which was considered to be hyperplasia of h-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
(41 reference statements)
2
17
0
Order By: Relevance
“…47 We have shown that humanized liver mice have aberrant liver-intestine bile acid signaling, a phenomenon which is likely present in all such models. For example, human hepatocyte repopulated uPA transgenic mice had livers 3 times the size of livers repopulated by rat hepatocytes, 23 but bile acids/signaling were not measured in this study. We anticipate that genetic correction (transgenic human FGF19) of bile acid signaling in this model will further extend its applicability to human diseases, especially relevant given the recent connection of Non-Alcoholic Fatty Liver Disease (NAFDL) to bile acid homeostasis and FGF19 signaling.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…47 We have shown that humanized liver mice have aberrant liver-intestine bile acid signaling, a phenomenon which is likely present in all such models. For example, human hepatocyte repopulated uPA transgenic mice had livers 3 times the size of livers repopulated by rat hepatocytes, 23 but bile acids/signaling were not measured in this study. We anticipate that genetic correction (transgenic human FGF19) of bile acid signaling in this model will further extend its applicability to human diseases, especially relevant given the recent connection of Non-Alcoholic Fatty Liver Disease (NAFDL) to bile acid homeostasis and FGF19 signaling.…”
Section: Discussionmentioning
confidence: 79%
“…We have previously noted that FRG and FRGN mice transplanted with human hepatocytes have large livers, roughly three times the expected size, similar to human chimeric livers in uPA/SCID mice. 23 When Fah + mouse donor hepatocytes were used to repopulate the liver, there was no difference in liver size between FRGN and FRGN19+ mice, and the repopulated livers were the expected size (~5% of body weight) (Fig. 2d).…”
Section: Resultsmentioning
confidence: 89%
“…In addition, a simple low tyrosine diet can be used as NTBC replacement 9,10 . The biochemical and histological characterization of repopulated uPA-transgenics and Fah knockouts has been well described 5,11 . Importantly, repopulated livers in both systems display normal function and morphology of human hepatocytes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Frozen sections were prepared from the livers of five h-GHtreated and 36 chimeric h-GH-untreated mice 6YF and stained with Oil Red O (ORO). When necessary, serial sections were stained with anti-h-CK8/18 antibodies (MP Biomedicals, Aurora, OH) that did not react with m-hepatocytes as previously described (19). Steatosis grading of h-hepatocytes was performed on ORO-stained chimeric mouse liver sections as follows: grade 0, no lipid droplets; grade 1, appearance of small lipid droplets; grade 2, small and middle-sized lipid droplets; grade 3, small to large droplets (Fig.…”
Section: Immunohistochemistry Lipid Staining and Grading Of Steatosmentioning
confidence: 99%